Can COVID-19 mark a tipping point for home-based telework? Conflict between untact technology and rigid institutions in Korea - Cho, Joonmo; Lee, Sanghee; Park, Byungjin (Frontiers in Public Health, 2023)
Previously, Korea showed a passive attitude toward home-based telework; however, this stance rapidly changed after the COVID-19 pandemic. Sustaining home-based telework entails adjusting productivity conditions, introducing performance-based evaluations, and modifying employment rules, as required by the Korean Labor Standards Act, which demand the consent of most workers. This study aims to explore the societal and institutional shifts necessary for ongoing home-based telework post-pandemic.This study discusses the sustainability of home-based work based on survey data and materials from institutions and previous research. It used data from the Workplace Panel Survey provided by the Korea Labor Institution for three years (2015, 2017, and 2019) to examine the status of home-based work and business responses. It also addresses legal issues related to changes in working conditions and worker-management agreements resulting from telework implementation. Legal aspects of telework are explained using relevant sections of Korea's labor laws.To establish home-based telework as a working method relevant to the Fourth Industrial Revolution after the pandemic, essential discussions are needed regarding its fundamental applicability to specific job sectors. Moreover, to activate home-based telework without deteriorating working conditions, achieving agreement between workers and management is imperative. However, legal complexities necessitate systemic changes for effective resolution.For the sustainable continuity of telework, a blend of societal awareness and institutional transformations is indispensable.The growth of home-based telework through untact technology expansion is hindered by inflexible Korean labor laws, judicial precedents, and worker-management relations. The absence of necessary legal and organizational changes could lead Korea to revert to prepandemic norms or slow implementation. Initially prevalent in IT, home-based telework has expanded across sectors due to the pandemic. Leading the "new normal," companies creatively enhance productivity through telework, but rigid systems and outdated cultures could impede post-pandemic progress.The study highlights the need for forward-looking institutional changes and adaptation to advancing technology. It provides valuable insights for organizations and policymakers to optimize work dynamics and enhance employee and employer well-being in the post-COVID-19 era.